Asia's low-carbon transition: Opportunities and challenges for trade - Sung-jin Kang; Donghyun Park (Asian Development Bank (ADB), 2023)
The central objective of our paper is to assess the opportunities and challenges for trade for Asian economies during the low-carbon transition. To do so, we examine the green trade patterns of Asian Development Bank member economies in the Asia and Pacific region between 1990 and 2019 based on three widely used green industry classifications, namely US BLS GGS, OECD ENV-TECH, and OECD CLEG classifications. Our analysis yields three key findings. First, the share of green goods in the exports of Asian economies has consistently increased since the early 2010s. Second, the share of Asian economies in global green exports has grown rapidly in recent years. Third, manufacturing products, especially machinery and electric equipment, account for the largest share of green trade. In fact, since the early 2010s, the shares of Asian economies in world manufacturing green exports and imports have increased. However, the green imports share showed faster growth than the exports share. Finally, the pattern of green trade differs depending on green industry definition, pointing to a need for international consensus on defining green trade in order to measure and analyze green trade patterns more accurately.
Keywords: F18; 330; low-carbon transition; green; trade; environment; Asia